2014
DOI: 10.1007/s11356-014-3405-7
|View full text |Cite
|
Sign up to set email alerts
|

Root morphological responses of three hot pepper cultivars to Cd exposure and their correlations with Cd accumulation

Abstract: Cultivars of hot pepper (Capsicum annuum L.) differ widely in their fruit cadmium (Cd) concentrations. Previously, we suggested that low-Cd cultivars are better able to prevent the translocation of Cd from roots to aboveground parts, but the corresponding mechanisms are still unknown. In this study, we aimed to improve understanding of the root morphological characteristics of the mechanisms involved in two low-Cd and a high-Cd cultivar. Seedlings were grown in nutrient solutions containing 0 (control), 2, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 76 publications
(19 citation statements)
references
References 25 publications
1
18
0
Order By: Relevance
“…Previous studies have identified low-Cd-accumulating genotypes of rice (Liu et al 2005), pepper (Huang et al 2015a), sweet potato (Huang et al 2015b), and Chinese cabbage (Liu et al 2010), which can grow in heavily contaminated sites and yield agricultural products with low Cd levels. Thus, the use of such genotypes is an effective and feasible measure to decrease dietary Cd exposure (Liu et al 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have identified low-Cd-accumulating genotypes of rice (Liu et al 2005), pepper (Huang et al 2015a), sweet potato (Huang et al 2015b), and Chinese cabbage (Liu et al 2010), which can grow in heavily contaminated sites and yield agricultural products with low Cd levels. Thus, the use of such genotypes is an effective and feasible measure to decrease dietary Cd exposure (Liu et al 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Liu, Probst & Liao (2005) attributed the lower Cd 2+ contents in the roots of S. alfedii to the smaller size of root system (smaller root length, surface area and volume). Huang et al (2015) also indicated that pepper cultivar with shorter roots, fewer root tips and smaller surface area had lower capacity for Cd 2+ uptake. Moreover, the tolerance of plants to Cd 2+ stress has also been assessed based on the content of H 2 O 2 produced when the plants were exposed to the stress.…”
Section: Discussionmentioning
confidence: 91%
“…Matching the mobilizing effect of roots in rhizospheric soil [43,44], higher leaching with vegetation cover in uncontaminated pots is expected, compared with uncultivated controls. Root morphology (surface area, diameter, tip density) generally plays an important role in nutrient and metal accumulation, especially for the less mobile Cd [45], and better tolerance to contamination should be expected when root distribution is moved downwards, as found in Sonchus and Tragopogon.…”
Section: Plant Responses To Metal Contaminants and Perspectives For Pmentioning
confidence: 99%